An introduction to Agile (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. For many years, project management has been dominated by the 'Waterfall' method, which focused on developing a detailed plan of action before commencing the actual development phase. With a Waterfall project, the end result is not delivered until the very end of the process. Agile takes a different outlook, focusing on breaking the project into smaller timeboxes and delivering something of value at the end of each one, which can then be analyzed and critiqued while the next timebox is already underway. In this track, we look at what Agile is, how it differs from other project management theories, and why it could work for you. Learning Objectives Learn what Agile is Learn how it differs from other project management approaches Learn why Agile suits some projects more than others.